Barron's SAT writing workbook - Ehrenhaft, George (Hauppauge, N.Y. : Barron's, 2006)
Presents a guide to studying for the essay portion of the new SAT, providing review chapters, practice correcting poorly written sentences, overview of test format, and more.
Includes index.
Young Adult
Keywords: English language -- Composition and exercises -- Examinations -- Study guides; Report writing -- Examinations -- Study guides; SAT (Educational test) -- Study guides; English language -- Composition and exercises -- Examinations -- Study guides; Report writing -- Examinations -- Study guides; SAT (Educational test) -- Study guides